Eats, shoots & leaves why, commas really do make a difference! - Truss, Lynne; Timmons, Bonnie (New York G.P. Putnam's Sons, 2006)
See how using (or not using) a comma can change the meaning of a sentence.
Keywords: English language -- Punctuation -- Juvenile literature; Comma -- Juvenile literature; English language -- Punctuation; Comma